IMPLIKASI TRANSFER FISKAL TERHADAP DISPARITAS INCOME - yuan williamson tamberan; Romualdus Turu Putra Maro Djanggo (Faculty Of Economics and Business, Musamus University, 2019)
This study aims to determine the implications of fiscal transfer to income disparity in Merauke Regency. The type of data used is time series data which began in 2010-2018 and the data collection was carried out using the documentation method sourced from the Central Statistics Agency of Merauke Regency and the Internet. Data were analyzed using regression analysis models with the help of SPSS 21 software. The results showed that partially or simultaneously fiscal transfers in the form of general allocation fund variables and special autonomy fund variables had a significant positive effect on income disparity variables in Merauke Regency. Keywords: fiscal transfer, income disparity, regional autonomy